The chloroplast membrane associated ceQORH putative quinone oxidoreductase reduces long-chain, stress-related oxidized lipids. (February 2016) - Curien, Gilles; Giustini, Cécile; Montillet, Jean-Luc; Mas-y-Mas, Sarah; Cobessi, David; Ferrer, Jean-Luc; Matringe, Michel; Grechkin, Alexander; Rolland, Norbert
Graphical abstract: Highlights: The biochemical activity of chloroplast ceQORH protein was unknown. ceQORH reduces the double bond of stress-related oxidized lipids named γ-ketols. ceQORH is a γ-ketol reductase identified in the chloroplast. Abstract: Under oxidative stress conditions the lipid constituents of cells can undergo oxidation whose frequent consequence is the production of highly reactive α, β-unsaturated carbonyls. These molecules are toxic because they can add to biomolecules (such as proteins and nucleic acids) and several enzyme activities cooperate to eliminate these reactive electrophile species. CeQORH (chloroplast envelope Quinone Oxidoreductase Homolog, At4g13010) is associated with the inner membrane of the chloroplast envelope and imported into the organelle by an alternative import pathway. In the present study, we show that the recombinant ceQORH exhibits the activity of a NADPH-dependent α, β-unsaturated oxoene reductase reducing the double bond of medium-chain ( C ⩾ 9) to long-chain (18 carbon atoms) reactive electrophile species deriving from poly-unsaturated fatty acid peroxides. The best substrates of ceQORH are 13-lipoxygenase-derived γ-ketols. γ-Ketols are spontaneously produced in the chloroplast from the unstable allene oxide formed in the biochemical pathway leading to 12-oxo-phytodienoic acid, a precursor of the defense hormone jasmonate. In chloroplasts, ceQORH could detoxify 13-lipoxygenase-derived γ-ketols at their production sites in the membranes. This finding opens new routes toward the understanding of γ-ketols role and detoxification.